Study of cationic and nonionic mixed micelles with NaBr and 3,5-Cl2C6H3CO2Na by use of probe nucleophilic reaction of piperidine with ionized phenyl salicylate - Fagge, Ibrahim Isah; Khalid, Khalisanni; Noh, Muhammad Azri Mohd; Yusof, Nor Saadah Mohd; Zain, Sharifuddin Md; Khan, Mohammad Niyaz (Japan Oil Chemists Society, 2018)
Behaviors of cationic and nonionic mixed micelles in the form of hexadecyltrimethylammonium bromide (HDABr) and hexadecyltrimethylammonium bromide-Polyethylene glycol hexadecyl ether (C16E20), in the presence of inert salts (NaBr and 3,5-dichlorosodium benzoate), by the use of reaction probe between Pp and ionized PhSH (Pp = piperidine and PhSH = phenyl salicylate), has been reported in this work. The values of RX Br (RX Br denotes ion exchange constants obtained in the presence of micelles of different structural features) or KX Br (KX Br denotes ion exchange constants obtained in the presence of micelles of the same structural features) for 3,5-Cl2C6H3CO2 - were almost the same at three different [HDABr]T (0.006, 0.010 and 0.015 M). The average value of RX Br or KX Br determined, in the presence of pure HDABr micelles, using semi empirical kinetic (SEK) method appeared to be almost 21/2-fold larger (RX Br or KX Br = 198) than that in the presence of mixed HDABr-C16E20 micelles (RX Br or KX Br = 78). Rheological measurements indicated the existence of wormlike/twisted micelles and vesicle at 0.015 M pure HDABr, various [3,5-Cl2C6H3CO2Na], and 25 and 35°C whereas there were evidence of only spherical micelles in the presence of mixed HDABr- C16E20 ([HDABr]T = 0.015 M and [C16E20]T = 0.006 M) at both temperatures.